How Expensive is Norway? : New International Relative Price Measures - Krajnyak, Kornelia (IMF Working Papers; Working Paper ;, 2010)
In this paper, we derive two new measures of international relative prices for Norway. Developments in these new measures follow rather closely movements in the CPI-based real effective exchange rate through the 1990s, but diverge after 2000-suggesting that the costs of living in Norway relative to its trading partners have risen in the recent years more than the real effective exchange rate would indicate.